PEMBERDAYAAN EKONOMI MASYARAKAT MISKIN DI YAYASAN PERJUANGAN WAHIDIYAH - Azis Muslim (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
Poverty is a miserable condition. Efforts to reduce poverty have been done by the government, but the results are not satisfied. Therefore, we need the involvement of other parties, such as religious institutions. This study aims to assess the involvement of Wahidiyah Struggle Foundation in tackling the problem of poverty through economic empowerment. The study focuses on the concept, implementation, and results of economic empowerment. Research uses qualitative method and collect data through observation, indepth interview, and documentation. Research found that Wahidiyah builds micro finance organizations as a central concept in economic empowerment. Their function is not only to increase financial capital, but also create solidarity among members. Strong solidarity among members was utilized to assist strengthening economic empowerment among themselves. This increase Wahidiyah member’s income significantly.